KUALITAS HIDUP DI KAWASAN AGLOMERASI EKONOMI PERKOTAAN BERDASARKAN EMPAT DIMENSI WELL-BEING : STUDI KASUS JALAN TERUSAN AMBARAWA KOTA MALANG - Wahyuningsih, Rani Destia; Hanifah, Rizki Arinda Nur; Shanti, Ni Putu Kumara; Alfarrez, Muhammad Dzaki; Rahmawati, Farida (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Agglomeration is an important role to increase social satisfaction and efficiency in the economy. The existence of agglomerations tend to occur in urban areas and become an interesting phenomenon to study. It is because agglomeration can cause productivity as well as welfare in society. This study aims to determine the quality of life in the economic agglomeration area based on the four dimensions well-being and find out the supporting and inhibiting factors of that quality of life. This research located in Terusan Ambarawa Street, Sumbersari, Lowokwaru District, Malang City, East Java. This research uses a qualitative approach, with primary and secondary data collected through observation, interviews, and literature review. The results showed society quality of life in the Terusan Ambarawa Street by four dimensions of well-being. These dimension are material well-being, emotional well-being, health and safety well-being, and community well-being. In addition, the results of this study identified several supporting and inhibiting factors for each dimension. The result of this study can be considered by the Malang City government in determining the next policy.